Implantation depth measured by 64-slice computed tomography is associated with permanent pacemaker requirement following transcatheter aortic valve implantation with the Core Valve® system. Issue 6 (June 2016) - Kammler, Jürgen; Blessberger, Hermann; Fellner, Franz; Kypta, Alexander; Lambert, Thomas; Engl, Magdalena; Hönig, Simon; Lichtenauer, Michael; Grund, Michael; Kerschner, Klaus; Saleh, Karim; Steinwender, Clemens
Abstract: Background: Patients undergoing transcatheter aortic valve implantation (TAVI) are at increased risk for post-interventional conduction disturbances leading to pacemaker (PM) implantation. We analyzed the association between implantation depth within the left ventricular outflow tract (LVOT), measured by 64-slice computed tomography (CT), and 'index electrocardiographic (ECG) changes' (new onset atrioventricular-block grade II or III or left bundle branch block with PR interval prolongation >200 ms). Methods: We evaluated patients who underwent TAVI with the Core Valve ® revalving system (Medtronic, Minneapolis, MN, USA) for treatment of severe aortic stenosis at our department. Patients with a prior PM implantation and patients for whom no CT scan was available after 3 months were excluded from analysis. We assessed implantation depth of the prosthesis within the LVOT as possible risk factors for the development of post-interventional 'index ECG changes' resulting in PM implantation and compared it with individual patient data as well as echocardiographic and electrocardiographic parameters. Results: The final study cohort comprised 53 patients for whom a 64-slice CT scan was available (mean age 81.7 ± 5.1 years, 36% male). Twenty-eight of these finally underwent PM implantation due to 'index ECG changes' within the first 48 hours after TAVI. Univariate logistic regression analysis could identify implantation depth of the prosthesis as the only significantly correlated risk factor for PM need in our cohort (OR 1.27, 95% CI: 1.08–1.51, p = 0.004). A cut-off value of 6 mm predicted this need with a sensitivity of 89% and specificity of 40%. Conclusion: Implantation depth of the Core Valve ® into the LVOT was associated with post-procedural PM requirement. Thereby, a cut-off value of 6 mm, as measured by 64-slice CT, proved useful to define patients at risk for PM requirement.